2015
DOI: 10.1371/journal.pone.0132529
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing Identifies a Missense Variant in EFEMP1 Co-Segregating in a Family with Autosomal Dominant Primary Open-Angle Glaucoma

Abstract: Primary open-angle glaucoma (POAG) is a clinically important and genetically heterogeneous cause of progressive vision loss as a result of retinal ganglion cell death. Here we have utilized trio-based, whole-exome sequencing to identify the genetic defect underlying an autosomal dominant form of adult-onset POAG segregating in an African-American family. Exome sequencing identified a novel missense variant (c.418C>T, p.Arg140Trp) in exon-5 of the gene coding for epidermal growth factor (EGF) containing fibulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 34 publications
5
44
0
5
Order By: Relevance
“…A missense mutation (p.Arg140Trp) was found in a 3-generation autosomal dominant African-American family with adult-onset, POAG (Mackay et al, 2015). EFEMP1 is expressed highly in mouse ciliary body and cornea, at lower levels in the retina.…”
Section: Genetic Linkage Analyses Of Poagmentioning
confidence: 99%
See 1 more Smart Citation
“…A missense mutation (p.Arg140Trp) was found in a 3-generation autosomal dominant African-American family with adult-onset, POAG (Mackay et al, 2015). EFEMP1 is expressed highly in mouse ciliary body and cornea, at lower levels in the retina.…”
Section: Genetic Linkage Analyses Of Poagmentioning
confidence: 99%
“…EFEMP1 is expressed highly in mouse ciliary body and cornea, at lower levels in the retina. The p.Arg140Trp mutation is located in the first of six calcium-binding EGF-like domains and may lead to abnormal accumulation of the mutant protein in the cell (Mackay et al, 2015). Mutations in EFEMP1 have been associated other ocular disorders including Doyne honeycomb retinal dystrophy and Malattia Leventinese (Hulleman, 2016; Marmorstein, 2004; Stone et al, 1999; Takeuchi et al, 2010).…”
Section: Genetic Linkage Analyses Of Poagmentioning
confidence: 99%
“…Fibulin-3 (F3) is a 55 kDa, secreted, extracelluar matrix glycoprotein that is produced in a number of tissues throughout the body, including the lung, skin, adipose tissue, and various cell layers within the eye such as the ciliary body (Mackay et al, 2015) and the retinal pigment epithelium (RPE) (Marmorstein et al, 2002). While the exact function of F3 is still not clear, removal of F3 in mice leads to a general, aging-associated phenotype including reduced lifespan, decreased body mass/fat and organ support failure (McLaughlin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, two independent studies have identified unique mutations in F3 associated with distinct eye diseases, reaffirming the notion that autosomal dominant genetic alterations in F3 have the ability to disrupt homeostasis in the eye. For example, in 2015, exome sequencing of a family with open-angle glaucoma identified an Arg140Trp (R140W) mutation in F3 (Mackay et al, 2015). Moreover, in 2016, additional sequencing efforts identified a Asp49Ala (D49A) mutation in F3 which was associated with cuticular drusen in an age-related macular degeneration (AMD) patient (Duvvari et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There is a large research community focusing on genetic variation study relating to human disease (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). This community often performs their analysis in-house rather than using any of the currently available tools for variant analysis.…”
Section: Introductionmentioning
confidence: 99%